Implementing Group Counseling to Change Student’s Insight Pattern about Learning in the Covid-19 Pandemic - Taufik Taufik (Universitas Muhammadiyah Barru, 2021)
The learning system that suddenly changes becomes a learning problem students experienced. The current research will reveal whether the application of group counseling during the Covid-19 pandemic can change students’ insight about the learning system and process. The research subjects are students of the VII grade and the VIII grade in a junior high school in Barru city. To determine the number of the sample, the researcher used purposive sampling technique with certain consideration, namely 15 students whose negative perception about the learning system during the Covid-19 pandemic condition. To collect data, researchers applied observation technique, distributed questionnaire, and took documents. The results of the current study indicate that after being given group guidance during several meetings, from those 15 students, 10 students (66.66%) strongly agree with the learning system applied in this Covid-19 pandemic condition, 5 students (33.33%) agree, there are no students who disagree and strongly disagree.